Religious Discrimination Among Working Women In Malaysia - Rafidah Hanim Mokhtar; Azizi Ayob; Asral Widad Ahmad Asnawi; Amira Ismail; Nur Hazlin Hazrin Chong; Mohd Eqwan Mohd Roslan; Azizah Che Awang; Siti Farhana Fathy; Norzila Baharin; Muhammad Farid Sulaiman; Hanan Othman; Siti Aishyah Sulaiman; et al. (Institut Sosial Malaysia (ISM), 2024)
Volume: 18 (page: 121-136)